2021
DOI: 10.1038/s41598-021-03801-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ocular demodicosis on the stability of the tear film and the tear break up time

Abstract: The aim of the study was to analyze the correlation between the presence of Demodex mites in the hair follicles of patients' eyelashes and the stability and break up time of the tear film assessed with the Non-Invasive Tear Break Up Times (NIBUT) method. 319 patients were included in the study (195 women, 124 men). The patients were divided into two groups: those with Demodex infestation and without visible symptoms of eyelid or eye surface diseases, and asymptomatic non-infested patients. The NIBUT analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In elderly Demodex-positive patients, CFS was more serious and FBUT was lower compared to negative patients. Sędzikowska et al showed that, in a study of patients without visible eyelid or eye surface disorders, the first and mean BUT in the Demodex-infested group was shorter than that in non-infected individuals [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In elderly Demodex-positive patients, CFS was more serious and FBUT was lower compared to negative patients. Sędzikowska et al showed that, in a study of patients without visible eyelid or eye surface disorders, the first and mean BUT in the Demodex-infested group was shorter than that in non-infected individuals [31].…”
Section: Discussionmentioning
confidence: 99%
“…In elderly Demodex -positive patients, CFS was more serious and FBUT was lower compared to negative patients. Sędzikowska et al showed that, in a study of patients without visible eyelid or eye surface disorders, the first and mean BUT in the Demodex -infested group was shorter than that in non-infected individuals [ 31 ]. Our results indicate a significant correlation between Demodex infestation and lower tear film stability and corneal epithelial injury in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular demodicosis increases with age, and is associated with eyelid disorders including anterior blepharitis, meibomian gland dysfunction (MGD), chalazia, and blepharo-keratoconjunctivitis in both adult and pediatric populations [2,3]. Tear film instability [4,5], pterygium recurrence [6], and rosacea have been linked to Demodex. Blepharitis was the first reported to be associated with ocular demodicosis in 1959 [7].…”
mentioning
confidence: 99%
“…Demodex folliculorum is more strongly associated with anterior blepharitis while Demodex brevis with MGD, recurrent chalazia, and refractory keratitis [2,8]. Demodex may reside as normal flora in healthy or asymptomatic diseased individuals [1,4] but become pathogenic when organism numbers reach a critical threshold, which are then sufficient to induce or exacerbate ocular symptoms. Higher numbers of Demodex have been noted in Demodex blepharitis (DB) compared to controls [2], however, the minimum number of Demodex required to induce symptoms remains unknown.…”
mentioning
confidence: 99%